2016
DOI: 10.1093/jxb/erw025
|View full text |Cite
|
Sign up to set email alerts
|

PME58 plays a role in pectin distribution during seed coat mucilage extrusion through homogalacturonan modification

Abstract: Highlight PME58 is the first pectin methylesterase gene identified to play a direct role in seed coat mucilage structure. Its activity influences pectin distribution upon mucilage extrusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 62 publications
(98 reference statements)
3
46
2
Order By: Relevance
“…Pectin is synthesized in the Golgi apparatus with HGs in a fully methylesterified status (Pelloux et al, 2007; Turbant et al, 2016). The de-methylesterification by PMEs is considered to facilitate the formation of the “egg-box” structures between HG molecules and Ca 2+ , which is deemed to be associated with an increase in cell wall rigidity (Micheli, 2001; Pelloux et al, 2007; Willats et al, 2001a; Willats et al, 2001b; Wolf et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pectin is synthesized in the Golgi apparatus with HGs in a fully methylesterified status (Pelloux et al, 2007; Turbant et al, 2016). The de-methylesterification by PMEs is considered to facilitate the formation of the “egg-box” structures between HG molecules and Ca 2+ , which is deemed to be associated with an increase in cell wall rigidity (Micheli, 2001; Pelloux et al, 2007; Willats et al, 2001a; Willats et al, 2001b; Wolf et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…PMEI6 , 14 , PME58 , FLY1 and SBT1.7 have been proved to be involved in HG de-methylesterification in the seed coat mucilage (Rautengarten et al, 2008; Saez-Aguayo et al, 2013; Shi et al, 2018; Turbant et al, 2016; Voiniciuc et al, 2013). In this study, we showed that PMEI13 and PMEI15 play a role in HG de-methylesterification in the seed mucilage, although PMEI15 might play only a supporting role (Supplemental Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations